(untitled) (Archives of Clinical Psychiatry, 2008)
BACKGROUND: Cloninger's Type 1/Type 2 classification is one of the most frequently studied alcoholism typologies. OBJECTIVES: To test the applicability of this typology, to characterize the identified subtypes and to evaluate their behavior in a therapeutic program. METHODS: Starting from variables described by Cloninger et al., 16 characteristics of 308 alcoholic men attending an outpatient treatment program were submitted to Cluster analysis for identification of two subgroups (clusters). Cross-tabulations were then performed to test for possible association of identified clusters to demographic and clinical variables. RESULTS: Patients belonging to cluster 1 were characterized by late onset of alcohol related problems, presented less social problems and greater guilt feelings concerning alcohol consumption. Cluster 2 included patients with more evident family history of alcoholism, antisocial characteristics, misuse of other psychoactive substances and lower level of adherence to treatment. DISCUSSION: Results identified the differential association of clusters to treatment and prognosis variables; overall, they were coherent to Type 1/Type 2 classification and give support to the concept that a simple diagnosis of alcohol dependence is not enough to respond to therapeutic needs of specific subgroups of patients.